Controlled deuterium labelling of imidazolium ionic liquids to probe the fine structure of the electrical double layer using neutron reflectometry. Issue 32 (15th July 2019) - Akutsu-Suyama, Kazuhiro; Cagnes, Marina; Tamura, Kazuhisa; Kanaya, Toshiji; Darwish, Tamim A.
Abstract : The electrical double layer structure formed in an ionic liquid electrolyte was determined by combining the neutron reflectivity and deuterium labelling techniques. Abstract : We combined the deuterium labeling and neutron reflectivity techniques to determine the fine structure of the electric double layer structure in an imidazolium ionic liquid (IL). For this, a simple and large scale deuteration method for imidazolium ILs was developed, where the deuteration level can be systematically controlled.